2023
DOI: 10.5253/arde.2022.a19
|View full text |Cite
|
Sign up to set email alerts
|

Savannah Trees Attract More Migratory Bird Species Than Residents, But Why?

Abstract: Arboreal bird species occurring in the wide transient zone between Sahara and tropical rain forest are unequally distributed across the rainfall zones. As this also holds for the woody plant species which they select for foraging, it is possible that birds are bound to specific rainfall zones because their preferred woody species are common there. But it may also be the other way around, i.e. that the distribution of birds is primarily determined by their selection of a specific rainfall zone, with the choice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The lines are dashed when connected to a longitudinal zone where birds were expected but not observed (thus ratio = 0). Observed bird densities are given in Supplementary Material of Zwarts et al (2023b) and observed and predicted densities in Figure 3 and Figures S5–S14 in Zwarts et al (2023f). χ 2 -tests show that longitudinal variation was in all cases significant ( P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The lines are dashed when connected to a longitudinal zone where birds were expected but not observed (thus ratio = 0). Observed bird densities are given in Supplementary Material of Zwarts et al (2023b) and observed and predicted densities in Figure 3 and Figures S5–S14 in Zwarts et al (2023f). χ 2 -tests show that longitudinal variation was in all cases significant ( P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…This allowed us to convert bird counts in the study sites into bird densities per ha, but also to calculate bird density per ha of canopy, separately per tree and shrub species. We used the distribution of different woody species (Zwarts et al 2023d) to formulate a prediction of bird distribution on the assumption that their density per ha of canopy in different woody species would be the same across their entire distribution areas and used the deviation of the observed from the predicted distribution to test whether the density of bird species varies per longitude; see Zwarts et al (2023f) for details.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data summarised in this paper will be used to address various related questions, notably (1) can the observed distribution be explained by the distribution of their preferred woody plants, and (2) if not, what other factors may be involved (Zwarts et al 2023c,e,f)?…”
Section: Discussionmentioning
confidence: 99%